IMPLEMENTASI PERATURAN DAERAH NOMOR 3 TAHUN 2013 PASAL 35TENTANG STANDARDISASI DAN SERTIFIKASI PROFESI USAHAAKOMODASI DI KABUPATEN BOGOR - Fuaddil, Muhammad; Surjana, Rahmat; Pranita, Diaz (UI Scholars Hub, 2017)
Indonesia is a country which is rich in natural and cultural importance in every region in Indonesia and the Regency of Bogor is one who has a wealth of it. Tourism in bogor Regency is one of the things that is important because it accounts for the third largest area of revenue. Bogor regency tourism has also become an effective tool inempowering and improving the economy of the community. The task of this final Work discusses the Implementation of local regulations No. 3 2013 article 35 concerning tourism. In the article mentioned that Standardization can be obtained by way of doing professional certification. To achieve that goal, the author during the process of drafting the final Paper Assignment using researchmethods collecting data, oral interview, obs ervation and the study of librarianship. From the results of this study revealed that the professional certification for trade facilitation has on accommodation by the Department of culture and tourism of the Bogor regency bekeja closely with the various parties concerned.